DAMPAK PERUBAHAN IKLIM TERHADAP PENDAPATAN PETANI SERTA PERAN EKONOMI SYARIAH DALAM MENDUKUNG KETAHANAN EKONOMI DI KABUPATEN TANGGAMUS - Dedi Rosadi; Mutiara Eka Putri; Pertiwi Utami (Andromeda : Jurnal Manajemen dan Bisnis Syariah, 2026)
This study aims to analyze the impact of climate change on farmers’ income, compare income conditions before and after climate change, and examine the role of Islamic economic principles in supporting farmers’ economic resilience in Tanggamus Regency. Climate change, characterized by unpredictable rainfall patterns, rising temperatures, and increasing extreme weather events, has significantly affected the agricultural sector, which is highly dependent on natural conditions. This study employs a qualitative method with a descriptive approach, where data were collected through in-depth interviews with farmers, agricultural extension officers, traders, farmer group leaders, and related government officials. Data analysis techniques include data reduction, data presentation, and systematic conclusion drawing. The results indicate that climate change negatively affects farmers’ income through decreased productivity, increased production costs, and price instability of agricultural products. Furthermore, there is a significant difference in farmers’ income conditions before and after climate change, where income was previously relatively stable but has become more fluctuating and declining afterward. In the context of economic resilience, Islamic economic principles such as profit-sharing, prohibition of riba (interest), mutual assistance (ta’awun), and instruments like zakat, infaq, and sadaqah play an important role in helping farmers cope with economic pressures. However, the implementation of these principles is still not optimal due to limited access, low financial literacy, and insufficient institutional support.